Manajemen Santri Dalam Menangani Scabies Di Pondok Pesantren Nurul Jadid - Nugroho, Setiyo Adi; Rahman, Abdur; Sholehah, Baitus (Universitas Nurul Jadid, 2023)
Introduction: Experience can be interpreted as something that has been experienced, lived or felt, both long ago and recently. Management is a process that consists of planning, organizing, mobilizing, and controlling to achieve predetermined goals. Management of students who are expected to be able to handle scabies.Research Methods: This qualitative research using purposive sampling method with a phenomenological approach aims to obtain in-depth information about the management experience of students in dealing with scabies at the Nurul Jadid Islamic Boarding School. Participants were selected based on research criteria and have been saturated. Data were collected by in-depth interviews and observations. Interpretative Phenomenological Analysis (IPA) is used in data analysis.Research Results: Five themes were identified in this study: (1) Handling students overcoming scabies using medical drugs (2) Handling students overcoming scabies using the existing culture in Islamic boarding schools (3) Perceptions of students overcoming scabies by sharing various ways (4) Feeling the many impacts of scabies on santri (5) There are many expectations of students when dealing with scabies.Conclusion: The results of this study, students are more confident in using topical drugs compared to oral and lack of facilities to carry out PHBS actions. For this reason, proper and adequate facilities are needed, as well as a quarantine program for students who have scabies.